Discussion of the Impact of Uncertainty Reporting on the Loan Decision - Bertholdt, Richard H. (Journal of Accounting Research, 1979)
Richard H. Bertholdt, Discussion of the Impact of Uncertainty Reporting on the Loan Decision, Journal of Accounting Research, Vol. 17, Studies on Auditing-Selections from the "Research Opportunities in Auditing" Program (1979), pp. 58-63